Metropolici Dyrrachion wobec naturalnych katastrof i kryzysu Bizancjum w XIII w. - Dudek, Jarosław (Vox Patrum, 2021)
In the 13th century, the bishops of Dyrrachion faced numerous political and religious problems. They also had to confront the natural disaster (earthquake and tsunami) that hit the city in 1271, subsequently abandoned by the bishop Niketas and conquered by the Latins. The historian Georgios Pachymeres described the course of the cataclysm and its aftermath, taking into account the criticism of the Church policy of Emperor Michael VIII Paleologos. In turn, for St. Serapion from distant Rus, the fate of the inhabitants of Dyrrachion, like the fate of the border town of Przemyśl, was a consequence of a moral decline caused by close contacts with Latins from Poland. Despite the opinion about the influence of Catholics in Dyrrachion, the support of the emperor from Constantinople ensured the protection of the Orthodox church organization in this part of the western Balkans.